Heavy metals content (Zn, Cu, Mn and Cd) in edible Turkish snail (Helix lucorum L.) in Skopje, Republic of North Macedonia - Mitev, Trajče; Dedov, Ivailo; Hristovski, Slavčo (Macedonian Journal of Ecology and Environment, 2019)
The results of heavy metals contents (Zn, Cu, Mn and Cd) in foot, shell and digestive gland (midgut gland or hepatopancreas) of Turkish snail (Helix lucorum L.) from 10 localities in Skopje region are presented in this paper and its value as food resource was assessed. Obtained results and their analysis shows that the distribution pattern of studied heavy metals in the organs of Turkish snail in different localities in Skopje follows basic physiological principles for this species. The highest content of Zn, Mn and Cu was detected in digestive gland as being the main storage organ. However, Cu content in digestive gland was comparable to the values in foot and shell pointing out that the digestive gland has lower potential to accumulate Cu. The values of Zn, Mn and Cu in our study are much lower than the ones recorded in other snail species in some polluted areas. Also, the concentration of Cd in foot was very low and thus it does not present any risk to human health in Skopje region when consummated.